Surface area of activated and modified charcoals obtained from agricultural resources Saccharum officinarum - Colpas C., Fredy; Tarón D., Arnulfo; González C., Rafael (Revista de Ciencias Agrícolas, 2017)
Activated charcoal is a material used in industry for absorbing gases and filtrates, cleansing liquids as well as for supporting catalysts in non-oxidative media. In addition, it is utilized in several environmental applications, such as in the absorption of metal lead ions. The objective of this work was the obtainment of activated charcoals by carbonizing sugarcane biomass at 400°C in a nitrogen atmosphere through activation with phosphoric acid and by oxidization with nitric acid or hydrogen peroxide followed by heat treatment. The preparation of activated charcoals from agricultural waste is being developed with excellent and potentially applicable results. In this context, a preparation method is shown using a chemical activation with phosphoric acid, which increased the content of carbon and decreased that of oxygen, then in order to study the development of surface area, it was put through an oxidation process with thermal heating. The charcoals obtained were characterized by proximal analysis, and diffuse reflectance infrared spectroscopy with Fourier transform was used for the determination of oxygenated functional groups. Basic oxygenated groups and acids were determined by means of Boehm’s method, while the BET method was used for the measurement of the surface area. The area of micropores was increased by treatment with HNO3 and H2O2 from 278m2/g up to 402 and 446m2/g, respectively. Most of the area on the charcoals was due to micropores. Charcoal pH was approximately 3 and COOH groups reached values of up to 2.12meq/g.